2011
DOI: 10.1016/j.hisfam.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and power: Age at first marriage and spousal age gap in lesser developed countries

Abstract: This paper examines age at first marriage for women and spousal age gap as an indicator for female agency from 1950 to 2005. Using a dataset of 77 LDCs this paper seeks to explore which variables determine differences at a country level in marriage patterns. We look at the influence of urbanisation, education, percentage population of Muslim faith, and family type. We find that education is a key in determining at what age women marry, having as would be expected a positive effect on age at first marriage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 21 publications
2
82
0
9
Order By: Relevance
“…Thus, this makes the men more dominant in decision making in the family circle. Findings by Carmichael (2011) are that larger spousal age gap in marriage disempowers the younger spouse in decisions in the household and the community at large due to lack of or inadequate self-confidence. Further, Guilbert (2013) notes that negative effect of larger spousal age gap on women empowerment is exacerbated with early marriages which is characterized by low education levels.…”
Section: Variablementioning
confidence: 99%
“…Thus, this makes the men more dominant in decision making in the family circle. Findings by Carmichael (2011) are that larger spousal age gap in marriage disempowers the younger spouse in decisions in the household and the community at large due to lack of or inadequate self-confidence. Further, Guilbert (2013) notes that negative effect of larger spousal age gap on women empowerment is exacerbated with early marriages which is characterized by low education levels.…”
Section: Variablementioning
confidence: 99%
“…Several studies have speculated on the role of urbanization, female labor force participation, and increase in female educational attainment as possible factors associated with this change (Singh and Samara, 1996;Garenne, 2004;Gyimah, 2009;Carmichael, 2011;Yu and Xie, 2015). Esteve et al (2013), however, found that women's age at union formation was not affected by educational expansion in Latin American countries.…”
Section: What Factors Determine the Age At Marriage? And What Factorsmentioning
confidence: 99%
“…In addition to the macro level of gender equality reflected in institutional arrangements, gender equality between partners is also found to play an important role in the contemporary fertility decision-making process (Mills et al 2008;Brodmann, Esping-Andersen, and Güell 2007). This equality involves different aspects, the most important of which seem to be the division between partners of paid and unpaid household labour (Miettinen, Lainiala, and Rotkirch 2015;Mills et al 2008;Matysiak and Vignoli 2008;Engelhardt, Kögel, and Prskawetz 2004), equality in the educational level of both partners (van Bavel 2012;Bauer and Jacob 2009), and partners' age gap (Carmichael 2011). All these characteristics are proxies for the power relationship between partners (Brodman, Esping-Andersen, and Güell 2007; Kim and Radoias 2014;Upadhyay et al 2014).…”
mentioning
confidence: 99%
“…Similarly, doing less unpaid household labour (so more time is left for paid work or pleasure) is associated with more power within a couple (Brines 1993). Finally, being older than the other partner translates into having more power due to having more experience and knowledge (Carmichael 2011).…”
mentioning
confidence: 99%